Volcanic crisis management supported by near real-time lava flow hazard assessment at Piton de la Fournaise, La Réunion - Chevrel, Magdalena Oryaëlle; Harris , Andrew; Peltier, Aline; Villeneuve, Nicolas; Coppola, Diego; Gouhier, Mathieu; Drenne, Stéphane (Volcanica, 2022)
Since 1979, Piton de la Fournaise (La Réunion) has erupted on average two times per year, with 95 % of these eruptions occurring within an uninhabited caldera. However, lava flows have occasionally impacted populated regions on the island, as in 1977 and 1986. Since 2014, an integrated satellite data–driven multinational response to effusive crises has been developed to rapidly assess lava inundation area and flow runout distance. In 2018, this protocol was implemented as a standalone software to provide a lava flow hazard map showing the probability of flow coverage and runouts as a function of discharge rate. Since 2019, the produced short-term hazard map is shared with local civil protection in the first few hours following the start of an eruption to aid in mitigation actions. Multiple exchanges between scientists, the observatory, and civil protection has improved the delivered hazard map, ensuring a common understanding, a product which is of use and usable, and helping to build effective mitigation strategies at Piton de la Fournaise. In this work we illustrate this effective near real-time protocol with case studies and document how the produced short-term hazard map has been tailored to meet the needs of civil protection.